Golden Bear at Long Beach Enroute Here from Mission - Unknown (Unknown)
The California Maritime Academy training ship Golden Bear arrived here last night, back from a goodwill trip to Italy, France, and Greece with a cargo of canned milk. Nearly half the cadets aboard, from Southern California communities, hurried ashore to greet friends and relatives. "It was sure a real thrill to see the kids in Italy because they were tickled just to be able to help carry some of the milk ashore," said Earl Warren, deck cadet and son of the Governor.